Interdisciplinary Research on the Bronze Age Diyala (Turnhout, Belgium)
ix, 107 sayfa
Keywords: “The Diyala region in eastern Iraq has long been a focal area of study for scholars of the Bronze Age, thanks both to its long history of human occupation, and its position as a site of strategic importance. Drawing on this strong tradition of scholarship and the results of numerous excavations and collections in the area, the seven contributions gathered in this volume aim to offer new insights into the cultures and societies of the Bronze Age Diyala by proposing new questions, problems, and approaches. Exploring subjects as widespread as architecture and iconography, cultural and economic history, the study of social networks, historiography, and the identification of ancient cities, these chapters explore the richness of the Bronze Age Diyala from a range of perspectives, and together offer important new insights into our understanding of the area.” --